Maternal Knowledge, Attitudes, And Practices and Health Outcomes of Their Preschool-Age Children in Urban and Rural Karnataka, India - Ramesh, Naveen; Cummings, Angela DL; Wagner, Norbert L; Izurieta, Ricardo O; Kwa, Boo H (National Journal of Community Medicine, 2016)
Introduction: Maternal knowledge, attitudes, and practices (KAP) impact child health. This evaluation, conducted by an organization providing health screenings at anganwadis (government-sponsored preschools) in south India, compared maternal KAP and health outcomes of their 2-5 year-old children. Methodology: An interview schedule was developed based on the National Family Health Survey (NFHS-3) questionnaires for this cross-sectional study. The random walk method guided data collection. Urban and rural mothers were interviewed and anthropometric measurements of their children collected. Scores were calculated for maternal KAP and child health. Results: Surveys were completed by 120 urban and 124 rural mothers. Mothers of children receiving health screenings had the highest mean attitude score. Children in convent schools were the healthiest, with the best child health scores, lowest incidence of ARI (12.7%) and diarrhea (5.5%), and the lowest prevalence of underweight (31.5%) and stunting (41.5%). Children not attending preschool had the highest incidence of diarrhea (25.0%) and greatest prevalence of stunting (59.4%). Conclusion: This evaluation allowed an organization providing health screenings to rural anganwadi children to compare those they serve to children in nearby communities. Identification of key questions predicting maternal practice guides future interventions with mothers.